2013
DOI: 10.1038/ni.2745
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional downregulation of S1pr1 is required for the establishment of resident memory CD8+ T cells

Abstract: Cell-mediated immunity critically depends on lymphocyte localization at sites of infection. While some memory T cells recirculate, a distinct lineage (resident memory T cells; TRM) are embedded in non-lymphoid tissues (NLTs) and mediate potent protective immunity. However, the defining transcriptional basis for TRM establishment is unknown. We report that CD8+ TRM cells lacked expression of the transcription factor KLF2 and its target gene S1pr1 (encoding sphingosine 1-phosphate receptor 1). Forced S1PR1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
772
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(824 citation statements)
references
References 53 publications
27
772
1
Order By: Relevance
“…It is interesting to note that in the recent hype about “tissue‐resident” memory T lymphocytes, bone marrow‐resident memory T lymphocytes were largely disregarded, quasi the “Cinderella” of memory lymphocytes 154, 155, 156, 157, 158, 159…”
Section: “Tissue‐resident” Vs Bone Marrow‐resident Memory T Lymphocytesmentioning
confidence: 99%
“…It is interesting to note that in the recent hype about “tissue‐resident” memory T lymphocytes, bone marrow‐resident memory T lymphocytes were largely disregarded, quasi the “Cinderella” of memory lymphocytes 154, 155, 156, 157, 158, 159…”
Section: “Tissue‐resident” Vs Bone Marrow‐resident Memory T Lymphocytesmentioning
confidence: 99%
“…CD69 has been shown to negatively regulate expression of sphingosine-1-phosphate receptor, which must be downregulated to establish tissue-residency, 19,20 whereas CD103 binds to the epithelial cell-expressed E-cadherin and is required for maintenance of intestinal T cells. 21 We found that HIC1-deficient CD4 þ and CD8 þ T cells in the LP and intraepithelial compartments expressed significantly reduced levels of CD69 and CD103 (Figures 2c and d).…”
Section: Hic1 Expression In Immune Cells Is Restricted To the Intestinementioning
confidence: 99%
“…In line with this, Ccr7 2/2 effector CD8 T cells introduced into uninfected skin fail to exit the injection site and, consequently, show enhanced local conversion into CD69 + CD103 + T RM cells (3). Other migration molecules, such as the sphingosine-1-phosphate (S1P) receptor S1P 1 , have been implicated in the regulation of peripheral T cell accumulation and long-term retention, although its precise function in this process remains to be determined (10,12,13). Effector T cells use S1P 1 to sense S1P gradients among blood, tissues, and lymph, thereby guiding entry into efferent lymphatics during egress from lymphoid tissues (14).…”
mentioning
confidence: 95%